Sistem Informasi Peminjaman Alat Di Laboratorium Otomasi Dan Robotik Fakultas Teknik Universitas Sebelas Maret Surakarta - Ali Mahfuliyanto (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
The Faculty of Engineering, Universitas Sebelas Maret (UNS) Surakarta has an information system to record data on borrowing tools in the automation and robotics laboratories, although they still use manual bookkeeping archives. This manual system has a weakness, namely it takes a lot of time to make a data report on borrowing tools. In addition, the existing tool lending system has not run optimally, so it is necessary to develop a system so that existing data can be integrated. The method used for the development of the tool lending system uses the System Development Life Cycle with the Waterfall model. The tool lending system is made using the PHP language and MySQL database as a data storage medium. The purpose of developing this information system is to speed up and simplify the process of borrowing tools, recaping data on borrowing tools, and making reports on borrowing laboratory equipment. This laboratory equipment loan system can be accessed by students, laboratory heads and admins. With the creation of the new system, it is hoped that it can assist and improve the performance of the UNS Faculty of Engineering staff, making it more effective and efficient in collecting data on borrowing tools in the automation and robotics laboratory.